(3GdLRGA GdJCOjHj aj bGfhf GdTQWI GdGJMGOj dOhdI GdEeGQGJ GdYQHjI GdeJMOI (B: s (3OQGSI ebGQfI eY GdbGfhf GdchjJj (B/ s - (3QGTO SYjO eMeO GdcfOjs; (3UHQi eMeO GdSfhSi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JJeKd CgejI gPg GdOQGSI aj GdJYQa Ydi ELQGAGJ JhbjY GdLRGA GdJCOjHj aj bGfhf GdTQWI ef NdGd OQGSI ebGQfI Hjf cd ef OhdI GdEeGQGJ GdYQHjI GdeJMOI hOhdI GdchjJ(B: (3MjK Ef GdLRGA GdJCOjHj dG Zfi Yfg(B: (3hdGSjeG aj eLGd GdYed GdTQWj GdPj jdRe efJSHjg HGdGfVHGW(B: (3hCj NWC bO jDOj Edi aTd GdLgGR GdCefj aj GdbjGe HOhQg GdeJeKd aj MaX GdCef hJMbjb GdGSJbQGQ aj GdeLJeY(B.(3hGYJeO GdHGMK Ydi GdefgL GdhUaj GdJMdjd GdebGQf(B.(3hJchfJ GdOQGSI ef KdGKI CHhGH hbO JhUd GdHGMK Edi YOI JhUjGJ CgegG VQhQI Jbfjf GdeNGdaGJ GdeSdcjI GdJCOjHnqjI(B: (3hPdc dNUhUjI GdYed GdTQWj hWHjYI GdLgGR GdTQWj(B: (3eY GdYed Ydi JWhjQ eLGdS GdJCOjH HeG jJfGSH eY GdfXQjGJ GdMOjKI ddJCOjH(B: (3hVeGf Mbhb GdOaGY hMb GdeJge HJhcjd eMGke eeGQS heSLd aj fbGHI GdeMGejf hYOe GbJUGQ Mb GdOaGY Ydi JYjjf HYV GdYGedjf aj GdLgGR GdTQWjs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2014s
(3HHdjhLQGajG(B: (3UaMGJ (B207-221s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdLRGA GdJCOjHj s; (3GdeNGdaGJ GdJGOjHjI s; (3GdJXde GdGOGQis; (3GdLQe GdJCOjHis; (3GdYbhHGJ GdJCOjHjIs; (3GdSdWI GdQFGSjIs; (3bGfhf GdTQWI GdGJMGOj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes